AB0048 CHARACTERIZING THE ROLE OF NET-DERIVED IL-33 IN SLE PATHOGENESIS. (June 2019) - Spiros, Georgakis; Papadaki, Garyfallia; Drakos, Elias; Giakopoulou, Charikleia; Eloranta, Maija-Leena; Ronnblom, Lars; Sidiropoulos, Prodromos; Verginis, Panayotis; Gkirtzimanaki, Aikaterini; Bertsias, George
Abstract : Background: Interleukin (IL)-33 is a cell necrosis-derived alarmin with immunostimulatory properties which depend on the context of immune cells and the inflammatory milieu (1). In Systemic Lupus Erythematosus (SLE), extracellular DNA (as in extracellular chromatin traps [NETs] or immune complexes [ICs]) combined with alarmins stimulate innate immunity receptors (such as Toll-like receptors [TLRs]) and the production of IFNa by plasmatocytoid dendritic cells (pDCs) (2, 3, 4). Objectives: We propose that IL-33 is a potential NET-decorating protein and we want to investigate its pro-inflammatory properties. Additionally, NETs could also act as a platform mediating IL33's bioactivity taking into consideration the excessive accumulation of proteases on extracellular traps. We hypothesize that NET-derived IL-33 might enhance the interferogenic capacity of pDCs. Methods: Peripheral blood polymorphonuclear cells (PMNs) were isolated from healthy and SLE individuals and their ability to form IL33-decorated NETs was assessed by confocal microscopy. Renal sections from active lupus nephritis patients were immunostained to observe any IL-33 decorated NETs. NET-supernatants from untreated and IC-treated SLE PMNs were administrated to healthy pDCs and type I IFN production was monitored by qPCR and ELISA. The contribution of IL-33 to the interferogenic capacity of NETs was assessed by pre-treating pDCs with a specific mAb against IL33-receptor (anti-ST2L). The effect of proteases on the IL33-mediated interferogenic potential of NETs was investigated by pharmaceutical inhibition of elastase and Cathepsin G. Results: Spontaneous-released NETs from peripheral blood PMNs of active SLE patients were decorated with IL-33 to larger extent as compared to healthy PMN NETs. IL-33 decorated NETs were observed in renal sections from active lupus nephritis patients exhibiting mainly tubulointerstitial localization. Treatment of SLE PMNs with ICs led to the release of NETs with extended IL-33 decoration and enhanced interferogenic capacity. IL33 receptor blockade significantly decreased the type I IFN response of NET-treated control pDCs. Elastase and Cathepsin G inhibition on NETs decreased the interferogenic capacity of IC-SLE NETs in an IL-33-dependent manner. Conclusion: NET-derived IL-33 is a novel mediator of the nucleic acid-driven aberrant type I IFN response which exacerbates SLE disease. NET structure may be crucial in regulating the bioactivity of IL-33. References: [1] Duan, et al. "The Role of IL-33 in Rheumatic Diseases." Clinical and Developmental Immunology (2013): 1-5 [2] Garcia-Romo, et al. "Netting Neutrophils Are Major Inducers of Type I IFN Production in Pediatric Systemic Lupus Erythematosus." Science Translational Medicine 3.73 (2011) [3] Lande R, et al. "Plasmacytoid dendritic cells sense self-DNA coupled with antimicrobial peptide." Nature (2007), Vol 449 [4] Tian, et al. "Toll-like Receptor 9–dependent Activation by DNA-containing Immune Complexes Is Mediated by HMGB1 and RAGE." Nature Immunology 8.5 (2007): 487-96 Acknowledgement: This phD research is funded by the "Strengthening Human Resources Research Potential via Doctorate Research" project implemented by State Scholarships Foundation (ΙκΥ) and co-financed by Greece and the European Union (European Social Fund- ESF) Disclosure of Interests: None declared